Rancang Bangun Sistem Informasi Manajemen Aset di Yayasan Perguruan Tinggi Flores (YAPERTIF) - Rainarius Gale Goa; Ferdinandus Lidang Witi; Melky Radja (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2022)
The development of technology is getting faster so that it forces people to use information Information Technology has had a tremendous impact, especially in the field of management. The old system is gradually being replaced by a newer system as a result of the development of increasingly advanced information technology, one of which is the use of a Management Information System which has become a necessity in an agency. Management information systems are typically used to process data, make information accurate, improve performance, and perform as expected. Asset management in Yapertif is less effective and efficient because it still uses Ms. Excel, which takes a long time to manage and search for asset data. when a large amount of data or asset information is needed, for example during accreditation or a request from Dikti, it takes more time to search. The solution to overcome the existing problems, the researchers took a study with the title